2018
DOI: 10.1080/17549507.2017.1416176
|View full text |Cite
|
Sign up to set email alerts
|

Vocal function exercises for normal voice: With and without semi-occlusion

Abstract: The SOVT posture used during VFEs is modifiable to a small extent without significantly undermining efficacy. Changes in MPT are less robust with reduced VT occlusion. Research in a clinical population is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…-----41-60 minutes (83,93,94) 1 to 2 hours (19,22,28,53,55,67,69,75,80,81,99,100) 2 to 5 hours (24,47) More than 5 hours (59,68,102,107) Information not available (17, 18, 21, 30, 31, 33, 34, 36-39, 49, 57, 58, 62, 64, 65, 70-72, 74, 76, 77, 79, 84-86, 98, 101, 104, 108-110)…”
Section: -40 Minutesmentioning
confidence: 99%
See 1 more Smart Citation
“…-----41-60 minutes (83,93,94) 1 to 2 hours (19,22,28,53,55,67,69,75,80,81,99,100) 2 to 5 hours (24,47) More than 5 hours (59,68,102,107) Information not available (17, 18, 21, 30, 31, 33, 34, 36-39, 49, 57, 58, 62, 64, 65, 70-72, 74, 76, 77, 79, 84-86, 98, 101, 104, 108-110)…”
Section: -40 Minutesmentioning
confidence: 99%
“…In SLH clinical practice, APE and acoustic analysis are the most used voice assessment procedures (3) . Of the 97 investigated studies, 12 reported changes in the participants' APE after the voice training (17,31,39,46,52,63,71,72,78,85,100,101) . In general, the degrees of hoarseness (56,57,62) and breathiness (31,52,56) decreased after the voice intervention.…”
Section: Tasks Sustained Vowel In Habitual Tonementioning
confidence: 99%
“…All have demonstrated efficacy with a range of effect sizes demonstrated across a variety of voice outcome measures; however, none have systematically evaluated the effect of each component or 'ingredient' in the treatment provided. Preliminary research investigating individual effects of components of VFE has isolated the therapeutic effects of practise dosage and the use of a semi-occluded vocal tract (nasal sound) [28,29]; however, this research was conducted in controlled experimental conditions with non-voice-disordered volunteers.…”
Section: What Is An Active Ingredient In Voice Therapy?mentioning
confidence: 99%
“…As it is described, it is the 'sound we make when we say yes', ergo, it is cueing a habitual phonatory task, while cueing only subtle muscular or physiological improvements in phonation. The use of features that prime improved vocal function, including a semi-occluded vocal tract [29], voice onset at resting expiratory level [91], and cueing for a clear and effortless voice [19], may not be sufficient in this technique as gross changes in voice quality and increased activation of muscles not usually activated in habitual phonation (e.g., low larynx and cricothyroid activation) are not cued. These features are, however, repeated in SVQ in which increased muscle activation and re-posturing of the larynx is also cued.…”
Section: Effects Of Optmentioning
confidence: 99%
“…), and resonant voice and conversation therapy for generalization of improved voice function to conversational speech or to address concomitant diagnoses such as muscle tension dysphonia. [22][23][24][25]…”
Section: Therapymentioning
confidence: 99%